# Solving the recurrence T(n) = 3T(n-2) with iterative method

It's been a while since I had to solve a recurrence and I wanted to make sure I understood the iterative method of solving these problems. Given:

$$T(n) = 3T(n-2)$$

My first step was to iteratively substitute terms to arrive at a general form:

$$T(n-2) = 3T(n-2 -2) = 3T(n-4)$$ $$T(n) = 3 *3T(n-4)$$

$$T(n) = 3^k T(n-2k)$$

Now I solve $n-2k = 1$ for $k$, which is the point where the recurrence stops (where $T(1)$) and insert that value ($n/2 - 1/2 = k$) into the general form:

$$T(n) = 3^{n/2-1/2}$$ $$T(n) = O(3^n)$$

I'm not sure about that last step:

I would just "argue" that as $n \to \infty$ one can ignore $-1/2$ and $n/2 \to n$ ? Is that assumption correct?

• You can drop the $-1/2$ upfront, as the $O$ notation absorbs constant factors. But $3^n$ is not proportional to $3^{n/2}$.
– user16034
Mar 14 at 7:50

Note that $3^{n/2-1/2} = \frac{1}{\sqrt{3}} 3^{n/2} = \frac 1{\sqrt{3}} \sqrt{3^n}$. So the $-\frac 12$ indeed becomes a constant factor that is absorbed by the $O()$, but $\frac n2$ in the exponent changes the base and changing the base changes the $O$-class.

The correct answer thus is $T(n) = O(3^{n/2}) = O(\sqrt{3^n})$.

• Thank you both @FrankW and @Jared! I marked this answer as correct because it contains an explanation (changing the base changes O-class).
– wpp
May 1, 2014 at 11:36

Everything was correct up until the last step...you found:

$$T(n) \propto 3^{\frac{n}{2}- \frac{1}{2}} = \left(3^{n - 1}\right)^{\frac{1}{2}} = \frac{1}{\sqrt{3}}\left(\sqrt{3}\right)^n$$

I have this one T(n)= 3T(n-2) +1 i wasn´t able to solve it if someone can please

– user16034
Mar 14 at 7:53

More rigorously:

First note that the recurrence only involves terms that are two units apart, so there will be a solution for the even $$n$$ and an independent one for the odd.

Let first $$n:=2m$$. We have

$$T(2m)=3T(2m-2)=3^2T(2m-2\cdot2)=\cdots3^mT(0)$$

or

$$T(n)=3^{n/2}T(0)=(3^{1/2})^nT(0)=\sqrt3^nT(0).$$ And similarly for odd $$n$$,

$$T(n)=\sqrt3^{n-1}T(1).$$

This is captured by

$$T(n)=\Theta(\sqrt3^n).$$